Security services of the NKVD-NKGB of Kabardino-Balkaria in the fight against German sabotage (1942-1944). - Azamat Tatarov (Кавказология, 2023)
The paper considers the most intense period of work of the People’s Commissariats of Internal Affairs and State Security (NKVD-NKGB) of Kabardino-Balkaria during the Great Patriotic War in their fight against Nazi German sabotage operations. It is shown that purposeful policy to destabilize the Soviet rear has overcome two stages. Security agencies had a hard time dealing with sabotage during the battle for the Caucasus between November 1943 and August 1944. Based on documentary materials, the author reveals the course of work of the NKVD-NGKB bodies in the fight against enemy agents, contribution of individual employees and population to security, special operations in the occupied area. The author concludes that, contrary to the statement of H. Himmler in 1944, sabotage in the Caucasus, including Kabardino-Balkaria, did not bring Berlin the expected results. The invisible front played an important role in maintaining stability of the Soviet rear anddestroying Nazi Germany’s plans to create a “fifth column” in Kabardino-Balkaria.